Concomitant head or neck injury increases risk of traumatic brain injury in facial fracture patients - Kokko, Linda-Lotta (Elsevier, 2025)
Concomitant traumatic brain injury (TBI) is common in facial fracture patients and prompt intervention is crucially important to minimize the risk of potential long-term sequalae. In order to achieve rapid diagnosis, the clinicians need to be aware of the risk factors associated with concomitant TBI and facial fractures. Previous literature suggests that a facial fracture can be considered a significant indicator of TBI. Nevertheless, a large data gap remains on specific injury patterns of facial fractures and associated TBI. Therefore, the objective of this study was to estimate and compare the frequency of and risk factors for TBI in patients with and without different types of additional injuries. The retrospective cohort study included 1836 facial fracture patients aged at least 18 years. Outcome variable was TBI with radiological finding in computed tomography or magnetic resonance imaging. The primary predictor variables were associated injury outside the head and neck, associated cranial fracture and associated neck injury. Based on this study, associated cranial fracture increased the risk for TBI 4.7-fold. Patients with associated neck injury had a 2.1-fold risk for TBI. In addition, significant predictors for TBI were increasing age (p=.0004), high energy of injury (p<.0001) and anticoagulant medication (p=.0003). Facial fracture patients with associated injuries in the head and neck region are in significant risk for TBI. In clinical work, multiprofessional evaluation of facial fracture patients should be routine and repeated survey should be targeted especially at high-risk patients to identify TBIs.